Assessing The Impact of Green Brand Positioning and Knowledge on Attitudes Towards Green Brands: A Study of Branded Coffee Consumer in Indonesia and Their Green Purchase Intentions - Lia, Della Ayu Zonna; Aninda, Maura Saskia (Program MM Universitas Surabaya, 2024)
Purpose: This research attempts to examine the nexus between Green Brand Positioning, Green Brand Knowledge, mediated by Attitude towards Green Brand, and their collective impact on Green PurchaseIntention among consumers of a specific coffee brand in Indonesia. Method: Data was collected from a sample of 296 individuals using an online questionnaire, employing a nonprobability sampling method and PLS-Structural Equation Model for analysis. Result: The study unveiled that while green brand positioning exhibited no influence on green purchase intention, the combined effect of green brand positioning, green brand knowledge, and attitudetowards green brand positively shapes green purchase intention. This highlights the capacity of companies embracing environmentally friendly practices to uphold their commitment to protecting the planet.Particularly in the realm of coffee brands, which have effectively engaged consumers in environmental consciousness, these companies serve as advocates for sustainability and earth preservation.Consequently, this underscores the importance for otherentrepreneurs, communities, and government to prioritize environmental stewardship and take proactive measures to safeguard the environment.